LOF Kirinyuh Leaves and Liquid Waste Tempeh with Pineapple Peel Bioactivator: Sensory and Macronutrient Content - Sekaringsih, Nur Jati; Asngad, Aminah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Liquid organic fertilizer is a liquid organic material that contains plant nutrients. Using liquid organic fertilizers can satiate the nutritional needs of plants and reduce the application of chemical fertilizers, which if used for an extended period, can damage the soil's organic structure. The purpose of this study is to determine the quality of liquid organic fertilizer made from kirinyuh leaves and tempeh liquid waste by adding a bioactivator derived from pineapple rind. The method applied is experimental, and use Completely Randomized Design with two factors. The first component is a mixture of kirinyuh leaves and tempeh effluent (K1=168 ml: 82 ml, K2=82 ml: 168 ml), and the second component is a bioactivator derived from ananas peel (B1=100 ml, B2=150 ml). Utilizing two-way ANOVA, qualitative and quantitative descriptive data research was conducted. Our field experiments showed that the N content was the highest in the treatment of K1B2 (1.02%), the P content was higher in the treatment of K2B1 (0.06 %), as well as the K content was highest in the treatments of K2B1 and K2B2 (0.10 %). The sensory quality of the average liquid organic fertilizer is brown, has a tapai aroma, and has a pH 4.6 – 5.